Religious Discourse in Modern Japan Religion, State, and Shintō - Isomae, Jun'ichi (Dynamics in the History of Religions, 2014)
Religious Discourse in Modern Japan explores the transportation of the Western concept of "religion" in in the modern era; the emergence of discourse on Shinto, philosophy, and Buddhism; and the evolution of the academic discipline of religious studies in Japan.; Readership: All interested in Japanese religion and modern Japan, especially State Shinto and the Emperor System, and anyone concerned with the concept of religion in terms of postcolonial conditions, postsecularism, and nation-state building in East Asia